Dynamics of anti-SARS-CoV-2 IgG antibodies over four months period during pandemic in health care workers - Jain, Amita; Verma, Anuragani; Shukla, Suruchi; Verma, Anil K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Person infected with severe acute respiratory syndrome- coronavirus-2 (SARS-CoV-2) may develop virus specific IgG antibodies but antibody titers might decline over time, antibody titer decline, chances of HCWs getting re-infected may be higher. Methods: Here we assessed status of Anti SARS-CoV-2 antibodies in HCWs over a four months period by detection of anti-SARS-CoV-2-IgG antibodies using a semi-quantitative enzyme-linked immunosorbent assay (ELISA). Results: The present follow up study shows that during four months period sero-positivity in HCWs increased from 32% to 42%. Of 100 enrolled HCWs, 37 were RT-PCR positive at least once, of which only 31 were seropositive and six were seronegative. Two HCWs turned sero negative from sero positive and in five HCWs antibody titer increased. Conclusions: Although HCWs are at a greater exposure risk, the sero-prevalence in them at places where adequate preventive measures are taken, is comparable to that of general population.